Performance Comparison of Wet Cell HHO Generator with Galvanized Steel and Stainless Steel Electrodes - Putri Pratiwi; Mastariyanto Perdana; Ahmad Fachrurrozi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2021)
The excessive use of fossil fuels has many negative impacts on the environment and health. Many studies have been conducted to find solutions to this problem, such as the use of oxy-hydrogen gas (HHO) as an alternative to reduce the use of fossil fuels as a source of energy in vehicles and other applications. The objective of this research is to compare the performance of a wet type HHO generator using two types of electrodes, stainless steel plate and galvanized steel plate. Both generators use nine electrodes with dimensions of 130 mm x 60 mm consisting of two plates at the positive pole (anode), one plate at the negative pole (cathode), and six neutral plates. Calculation of the power consumed by the HHO generators, the flow rate of the gas produced, and the efficiency of these generators are carried out to compare the performance of both HHO generators. The results showed that the performance of the HHO generator using stainless steel plate as an electrode was better than galvanized steel which was indicated by a higher efficiency value.